2017
DOI: 10.3892/etm.2017.5157
|View full text |Cite
|
Sign up to set email alerts
|

A novel effective chemical hemin for the treatment of acute carbon monoxide poisoning in mice

Abstract: There is no effective drug for the therapy of acute carbon monoxide (CO) poisoning. The purpose of the present study was to investigate the potential preventive and therapeutic effects of hemin on an animal model of acute CO poisoning and to provide a potential therapeutic candidate drug. A total of 80 Kunming mice were randomly divided into four groups, namely the air control, acute CO poisoning, hemin-treatment + CO and hemin-pretreatment + CO groups (n=20 each). Furthermore, the mortality rate of mice, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, it has been reported that HO-1 induction decreases inflammation, inhibits platelet aggregation, and increases fibrinolysis and phagocytosis, thus preventing tissue damage, thrombosis and sepsis [ 184 ]. Additionally, hemin is an activator of neuroglobin, a protein involved in oxygen transport and storage in neurons that increases oxygen’s intracellular partial pressure in neurons, and is crucial to protect neurons from hypoxic injury [ 185 , 186 , 187 ]. In addition, as mentioned above, HO-1 has a reported antiviral activity against multiple viruses.…”
Section: Ho-1 Induction As a Strategy Against Covid-19mentioning
confidence: 99%
“…For example, it has been reported that HO-1 induction decreases inflammation, inhibits platelet aggregation, and increases fibrinolysis and phagocytosis, thus preventing tissue damage, thrombosis and sepsis [ 184 ]. Additionally, hemin is an activator of neuroglobin, a protein involved in oxygen transport and storage in neurons that increases oxygen’s intracellular partial pressure in neurons, and is crucial to protect neurons from hypoxic injury [ 185 , 186 , 187 ]. In addition, as mentioned above, HO-1 has a reported antiviral activity against multiple viruses.…”
Section: Ho-1 Induction As a Strategy Against Covid-19mentioning
confidence: 99%
“…Another study conducted a preclinical trial using mice exposed to CO. 8 Hemin administration significantly reduced the mortality rate, improved symptoms of acute CO poisoning, and reduced the level of COHb and serum concentration of MDA. Histologically, in the group without treatment, it was observed that there was inflammation of the cells in the CA1 region of the hippocampus and that the number of pyramidal cells was lower.…”
Section: New Therapies In Preclinical Studiesmentioning
confidence: 91%
“…Guan et al 7 Animal experimentation Hemin Hemin prevents the lesion of the hippocampus after CO poisoning and increases survival at 24 h from CO exposure Li et al 8 Animal experimentation Hemin Hemin improved symptoms of CO poisoning, reduced the level of COHb and the serum concentration of MDA Li et al 9 Animal experimentation NBP NBP may inhibit CO-induced early neuronal apoptosis Bi et al 10 Animal experimentation NBP NBP may alleviate damage to the hippocampus produced by CO Wang et al 11 Prospective essay NBP þ MSCT versus NBP versus MSCT Best results in MRI and cognitive tests with combined therapy with NBP or only MSCT Xiang et al 12 Randomized, doubleblind, prospective trial NBP + HBOT Best results in cognitive tests with NBP þ HBOT combined therapy Roderique et al 13 Animal experimentation…”
Section: Studio Type Treatment Main Findingsmentioning
confidence: 99%